Photodynamic therapy: a new concept in medical treatment - Sibata,C.H. (2000)
A new concept in the therapy of both neoplastic and non-neoplastic diseases is discussed in this article. Photodynamic therapy (PDT) involves light activation, in the presence of molecular oxygen, of certain dyes that are taken up by the target tissue. These dyes are termed photosensitizers. The mechanism of interaction of the photosensitizers and light is discussed, along with the effects produced in the target tissue. The present status of clinical PDT is discussed along with the newer photosensitizers being used and their clinical roles. Despite the promising results from earlier clinical trials of PDT, considerable additional work is needed to bring this new modality of treatment into modern clinical practice. Improvements in the area of light source delivery, light dosimetry and the computation of models of treatment are necessary to standardize treatments and ensure proper treatment delivery. Finally, quality assurance issues in the treatment process should be introduced.